2011
DOI: 10.1002/dvdy.22658
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest cells retain their capability for multipotential differentiation even after lineage‐restricted stages

Abstract: Multipotency of neural crest cells (NC cells) is thought to be a transient phase at the early stage of their generation; after NC cells emerge from the neural tube, they are specified into the lineage‐restricted precursors. We analyzed the differentiation of early‐stage NC‐like cells derived from Sox10‐IRES‐Venus ES cells, where the expression of Sox10 can be visualized with a fluorescent protein. Unexpectedly, both the Sox10+/Kit− cells and the Sox10+/Kit+ cells, which were restricted in vivo to the neuron (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…Both types of cells were shown to differentiate into neurons, glial cells, and melanocytes. These results support the concept that NCCs maintain their multipotency even after emerging from the neural tube regardless of their migratory pathways (Motohashi et al, ).…”
Section: Introductionsupporting
confidence: 88%
“…Both types of cells were shown to differentiate into neurons, glial cells, and melanocytes. These results support the concept that NCCs maintain their multipotency even after emerging from the neural tube regardless of their migratory pathways (Motohashi et al, ).…”
Section: Introductionsupporting
confidence: 88%
“…1A); P2, P6, P14, adult anagen III/IV (7dpp) and adult catagen VII (21 days post plucking, 21dpp). Despite the availability of a number of useful fluorescent Sox10 reporter mice [26][28], we opted to characterize protein expression with immunolabeling as this method is applicable to non-transgenic mouse studies. Using antibodies, we observed that nearly all DCT + cells within hairs co-express SOX10 regardless of time point, location or differentiation status (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whether MBs fundamentally possess the multipotency or monopotent MBs are induced to become multipotent by their surroundings is presently unknown. We previously showed that the multipotency of NCCs was retained just after delaminating from the neural tubes and after migrating to their targeting tissues (Motohashi et al, ). This finding suggests that the multipotency of NCC is continuously retained in their derivatives, allowing us to speculate that the multipotency of MBs is an intrinsic character.…”
Section: Discussionmentioning
confidence: 99%